Efficacy and safety of deferasirox in non-thalassemic patients with elevated ferritin levels after allogeneic hematopoietic stem cell transplantation - Jaekel, Nadja; Lieder, K.; Albrecht, S.; Leismann, O.; Hubert, K.; Bug, G.; Kröger, N.; Platzbecker, U.; Stadler, M.; Haas, K. de; Altamura, Sandro; Muckenthaler, Martina; et al. (Bone marrow transplantation, 2016)
Elevated serum ferritin contributes to treatment-related morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). The multicenter DE02 trial assessed the safety, efficacy and impact of deferasirox on iron homeostasis after allogeneic HSCT. Deferasirox was administered at a starting dose of 10 mg/kg per day to 76 recipients of allogeneic HSCT, with subsequent dose adjustments based on efficacy and safety. Deferasirox was initiated at a median of 168 days after HSCT, with 84% of patients still on immunosuppression. Baseline serum ferritin declined from 2045 to 957 ng/mL. Deferasirox induced a negative iron balance in 84% of patients. Hemoglobin increased in the first 3 months, and trough serum cyclosporine levels were stable. Median exposure was 330 days, with a median compliance rate of >80%. The most common investigator-reported drug-related adverse events (AEs) were increased blood creatinine (26.5%), nausea (9.0%) and abdominal discomfort (8.3%). Fifty-four (71.1%) patients experienced drug-related AEs, which occasionally resulted in discontinuation (gastrointestinal (n=6), skin (n=3), elevated transaminases (n=1) and creatinine (n=1)). The incidence of AEs appeared to be dose related, with 7.5 mg/kg per day being the best-tolerated dose. Low-dose deferasirox is an effective chelation therapy after allogeneic HSCT, with a manageable safety profile, even in patients receiving cyclosporine.
Published online 14 September 2015
Gesehen am 30.04.2020